Cardiomyocyte differentiation of pluripotent stem cells with SB203580 analogues correlates with Wnt pathway CK1 inhibition independent of p38 MAPK signaling. (March 2015) - Laco, Filip; Low, Joo-Leng; Seow, Jasmin; Woo, Tsung Liang; Zhong, Qixing; Seayad, Jayasree; Liu, Zhenfeng; Wei, Heiming; Reuveny, Shaul; Elliott, David A.; Chai, Christina L.L.; Oh, Steve K.W.
Abstract: Differentiation of human pluripotent stem cells as embryoid bodies (EBs) has been achieved previously with p38alfa MAPK inhibitors such as SB203580 with moderate efficiency of 10–15%. We synthesized and screened 42 compounds that are 2, 4, 5-trisubstituted azole analogues of SB203580 for efficient cardiomyocyte differentiation. Our screen identified novel compounds that have similar cardiac differentiation activity as SB203580. However, the cardiac differentiation did not correlate with p38alfa MAPK inhibition, indicating an alternative mechanism in cardiac differentiation. Upon profiling several 2, 4, 5-trisubstituted azole compounds against a panel of 97 kinases we identified several off targets, among them casein kinases 1 (CK1). The cardiomyogenic activities of SB203580 and its analogues showed a correlation with post mesoderm Wnt/beta-catenin pathway inhibition of CK1 epsilon and delta. These findings united the mechanism of 2, 4, 5-trisubstituted azole with the current theory of Wnt/beta-catenin regulated pathway of cardiac differentiation. Consequently an efficient cardiomyocyte protocol was developed with Wnt activator CHIR99021 and 2, 4, 5-trisubstituted azoles to give high yields of 50–70% cardiomyocytes and a 2-fold increase in growth. Graphical abstract: Highlights: Novel Tri-substituted Azoles (TAs) based on p38 MAPK inhibition were synthesized to induce potent cardiac differentiation. But p38 MAPK inhibition did not correlate with cardiogenesis potential. Novel TAs however, inhibited CK1 effectively. CK1 inhibition resulted in reduced Wnt signaling, which induced post mesoderm cardiac differentiation. TA inhibitors improved cell growth in comparison to other Wnt inhibitors during cardiac differentiation.